2020
DOI: 10.1186/s12877-020-01577-w
|View full text |Cite
|
Sign up to set email alerts
|

Web-based exercise versus supervised exercise for decreasing visceral adipose tissue in older adults with central obesity: a randomized controlled trial

Abstract: Background: Visceral adipose tissue (VAT) is a strong risk factor for cardiovascular disease and increases with age. While supervised exercise (SE) may be an effective approach, web-based exercise (WE) have other advantages such as being more readily accessible. Therefore, we evaluated the effects of WE on VAT, body composition and cardiometabolic risk markers in centrally obese older adults and compared the effects of WE to SE. We also explored the feasibility of WE. Methods: In a randomized controlled trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…The summary of analysis is provided in Table 3, which lists the themes/observations from reviewers that correspond with the objective statement and sorts articles from the most recent to the oldest. [25] Not reported Convenience of telemedicine, increased patientprovider communication, concerns adequately addressed, increased access Strong satisfaction Richards et al [24] Some patients prefer in-person consultations, technical literacy Pandemic created acceptance of technology, past experience with technology Not reported Kurihara et al [23] Technology needs further development, technical literacy Technical literacy, past experience with technology, perceived usefulness, increased patient-provider communication, perceived ease of use Not reported Alkirie et al [26] Technology needs further development Increased connectedness, self-management, flexibility, and access Not reported Ballin et al [27] Health literacy, availability of technology, technical literacy Enabled social interaction; decreased anxiety; increased connectedness, technical literacy, and access; televideo enables reading of body language; education; convenience of telemedicine Not reported Banbury et al [28] Technology needs further development, decrease in patient-provider communication, technical literacy, confidentiality/security Increased efficiency, access, and patient-provider communication, and improved standard of care Not reported Barnett et al [29] Discomfort for wearable monitors, technical literacy, technology needs further development Technical literacy, increased self-management, increased access, increased flexibility Not reported Batalik et al [30] Limits of reimbursement for telemedicine, some patients prefer in-person consultations, connectivity, technical literacy Pandemic created acceptance of technology, availability of technology, fewer miles driven to appointment, convenience of telemedicine, faster initiation of treatment, decreased costs Not reported Beller et al [31] Perceived lack of usefulness, lack of personal desire to get better, some patients prefer inperson consultations Increased connectedness, increased adherence, improved health behaviors Not reported Bernabe-Ortiz et al [32] Not reported Pandemic created acceptance of technology Not reported Bilgrami et al [33] Decrease in quality of life after intervention Perceived usefulness, perceived ease of use, increased adherence Strong satisfaction Broers et al [34] Technical literacy, availability of technology Increased adherence, increased self-management, increased weight loss, technical literacy Not reported Cho et al [35] Technology needs further development Technical literacy, perceived ease of use Not reported Claes et al [36] Lack of personal desire to get better, technology needs further development, technical literacy Increased adherence, increased self-management Not reported Coorey et al [37] Technology needs fur...…”
Section: Thematic Analysis Based On Results Of Individual Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The summary of analysis is provided in Table 3, which lists the themes/observations from reviewers that correspond with the objective statement and sorts articles from the most recent to the oldest. [25] Not reported Convenience of telemedicine, increased patientprovider communication, concerns adequately addressed, increased access Strong satisfaction Richards et al [24] Some patients prefer in-person consultations, technical literacy Pandemic created acceptance of technology, past experience with technology Not reported Kurihara et al [23] Technology needs further development, technical literacy Technical literacy, past experience with technology, perceived usefulness, increased patient-provider communication, perceived ease of use Not reported Alkirie et al [26] Technology needs further development Increased connectedness, self-management, flexibility, and access Not reported Ballin et al [27] Health literacy, availability of technology, technical literacy Enabled social interaction; decreased anxiety; increased connectedness, technical literacy, and access; televideo enables reading of body language; education; convenience of telemedicine Not reported Banbury et al [28] Technology needs further development, decrease in patient-provider communication, technical literacy, confidentiality/security Increased efficiency, access, and patient-provider communication, and improved standard of care Not reported Barnett et al [29] Discomfort for wearable monitors, technical literacy, technology needs further development Technical literacy, increased self-management, increased access, increased flexibility Not reported Batalik et al [30] Limits of reimbursement for telemedicine, some patients prefer in-person consultations, connectivity, technical literacy Pandemic created acceptance of technology, availability of technology, fewer miles driven to appointment, convenience of telemedicine, faster initiation of treatment, decreased costs Not reported Beller et al [31] Perceived lack of usefulness, lack of personal desire to get better, some patients prefer inperson consultations Increased connectedness, increased adherence, improved health behaviors Not reported Bernabe-Ortiz et al [32] Not reported Pandemic created acceptance of technology Not reported Bilgrami et al [33] Decrease in quality of life after intervention Perceived usefulness, perceived ease of use, increased adherence Strong satisfaction Broers et al [34] Technical literacy, availability of technology Increased adherence, increased self-management, increased weight loss, technical literacy Not reported Cho et al [35] Technology needs further development Technical literacy, perceived ease of use Not reported Claes et al [36] Lack of personal desire to get better, technology needs further development, technical literacy Increased adherence, increased self-management Not reported Coorey et al [37] Technology needs fur...…”
Section: Thematic Analysis Based On Results Of Individual Studiesmentioning
confidence: 99%
“…Occurrence, n (%) References Themes/observations 12 (9.1) [27,30,35,37,38,40,41,45,46,49,57,58] Increased self-management 11 (8.3) [23,25,31,33,41,43,47,51,52,61,62] Pandemic created acceptance of technology 10 (7.6) [32,34,35,37,38,40,43,46,58,67] Increased adherence 9 (6.8) [24,[27][28][29][30]41,52,53,60] Increased access 8 (6.1) [49,50,54,55,[62][63][64]66] Increased social support 7 (5.3) ...…”
Section: Table 4 Facilitator Themes and Individual Observations (N=132)mentioning
confidence: 99%
See 1 more Smart Citation
“…A finding from this review that stands in contrast to those of previous reviews in exercise oncology is that a higher percentage of unsupervised interventions (56%; those without face-to-face interaction) were successful at increasing PA levels compared with those that were partially supervised (41%; those with one or more face-to-face components) [ 7 , 119 ]. This may be because of feelings of autonomy promoted by unsupervised interventions, a factor that has been linked to increased intrinsic motivation and PA behavior change [ 120 - 122 ]. In addition, it may be in part because of the more frequent use of behavioral theories (unsupervised: 63%; supervised: 56%) and BCTs (unsupervised mean: 13.8; supervised mean: 11.8) in the included unsupervised interventions, which have been associated with effectiveness in web-based behavioral interventions [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mobile health (mHealth) facilities (smartphone-based educational apps, web-based tools, SMS text messaging, PDA physiological status monitoring, and connected captors) improved the delivery of the components of rehabilitation when taken individually [ 22 ]. In patients with obesity, a 10-week web-based exercise program has shown a significant effect on patients’ FM [ 23 ]. In addition, mHealth nutrition management or therapeutic education had significant effects on body weight (BW) and BMI in obesity [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%